The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.jspd.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

At What Levels Are Freehand Pedicle Screws More Frequently Malpositioned in Children?

Abstract: Level IV, Therapeutic Study. See the Guidelines for Authors for a complete description of the levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Lehman et al found 10.5% screws placed using the freehand technique were malpositioned on CT imaging 16 . Baghdadi et al found 9% of screws placed in children with freehand technique had more than a 4 mm breach, and up to 20% may have a 2 mm breach 17,18 . Samdani et al also found that 12% of freehand screws had a > 2 mm breach, with no statistical correlation based on surgeon experience 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Lehman et al found 10.5% screws placed using the freehand technique were malpositioned on CT imaging 16 . Baghdadi et al found 9% of screws placed in children with freehand technique had more than a 4 mm breach, and up to 20% may have a 2 mm breach 17,18 . Samdani et al also found that 12% of freehand screws had a > 2 mm breach, with no statistical correlation based on surgeon experience 19 .…”
Section: Discussionmentioning
confidence: 99%
“…While with the screw related complications, image guided approach did not show much advantage over free-hand technique [29] . Also, prior studies have reported that 5–17% pedicle screws are malpositioned, but these studies were not purely focused on children with younger age groups(12 years and less) [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Three of these leaks occurred at the upper end of the construct and were all at the right upper thoracic area, which is known to have a high occurrence of small (type C and D) pedicles and highest rate of screw malposition (23, 24). Interestingly, the presentation was delayed.…”
Section: Discussionmentioning
confidence: 99%